2014
DOI: 10.3892/or.2014.2982
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead-box A1 suppresses the progression of endometrial cancer via crosstalk with estrogen receptor α

Abstract: Mechanisms governing the function of Forkhead-box A1 (FOXA1), a member of the FOX class of transcription factors, have been extensively studied. However, little is known about the activities and expression pattern of FOXA1 in endometrial cancer (EC). In the present study, we investigated the level of FOXA1 in multiple human EC cell lines and clinical samples by immunohistochemistry, qRT-PCR and Western blot analysis. FOXA1 overexpression was observed in estrogen receptor (ER)α-positive EC cell lines (P=0.0048)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…Primary fresh tissues were obtained from patients immediately after surgical removal and were snap-frozen in liquid nitrogen for storage prior to further use. The IHC protocol was performed as previously described (4).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Primary fresh tissues were obtained from patients immediately after surgical removal and were snap-frozen in liquid nitrogen for storage prior to further use. The IHC protocol was performed as previously described (4).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, we found that FOXA1 was significantly downregulated in EC tissues compared to that noted in normal endometrium (4). To further assess the role of FOXA1 in EC, we compared FOXA1 expression with prognostic factors in normal endometrium and EC tissues using initial reverse transcription-quantitative PCR (RT-qPCR) and IHC analyses.…”
Section: Foxa1 Overexpression Is Associated With Good Prognosis In Ecmentioning
confidence: 99%
See 3 more Smart Citations